New species and genus of Columbellidae (Gastropoda: Buccinoidea) from the Western Pacific - Monsecour, Kevin; Raines, Bret K. (Zootaxa, 2024)
Ten new species and one new genus of Columbellidae from several Pacific Islands are introduced as new to science. The following species originating from Saipan, Northern Marianas are described: Ascalista saipanensis sp. nov., Mitrella harryleei sp. nov., Mitropsis noduliferus sp. nov., Retizafra praefulgida sp. nov. and Zafra spadicea sp. nov. Euspiralta okinawaensis sp. nov. originates from Okinawa, Japan. Zafra fijiensis sp. nov. originates from Fiji. From Wake Atoll the species Mokumea gracilicostata sp. nov., Speirazafra wakensis gen. nov. et sp. nov. and Zafra thaanumi sp. nov..